THE ROLE AND SIGNIFICANCE OF FACTORING AGREEMENTS IN INTERNATIONAL SALES CONTRACTS: NATIONAL AND FOREIGN EXPERIENCE - Nomozov Khusan Akhmat o‘g‘li; Eshmurzayev Umar Umidovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article examines the role and significance of factoring in international sales contracts. The research is based primarily on two legal sources: the 1988 UNIDROIT Convention on International Factoring and the 2023 Model Law on Factoring. These documents describe factoring as a financial mechanism that combines receivables assignment, financing, and debt collection. The Convention clearly regulates key issues such as the assignment of receivables, notification to the debtor, and the invalidity of contractual clauses restricting assignment. Practical sources show that factoring helps exporters accelerate payments, reduce risks, and simplify trade procedures. The article also evaluates the advantages and potential challenges of this mechanism, along with the opportunities for its application in Uzbekistan.